THE EFFECTIVENESS OF COMMUNICATION AND INFORMATION SERVICE GROUP COMMUNICATION IN THE DISSEMINATION OF DEVELOPMENT INNOVATIONS IN NORTH SUMATRA PROVINCE - Alfikri, Muhammad (International Journal of Islamic Education, Research and Multiculturalism (IJIERM), 2021)
Abstract: This study aims to determine the Effectiveness of Communication And Information Service Group Communication in the Spread of Development Innovation in North Sumatra Province, Jalan H. Muhammad Said No.27 Medan. The focus of this study is How is the effectiveness of group communication of the Communication and Informatics Service of North Sumatra Province in spreading innovation? This research uses a qualitative approach through the design of the Case Study model. The results of this study are the activity of group communication in the dissemination of innovations in the development of North Sumatra, through various techniques. Meanwhile, the effectiveness and communication strategy of the group how to process the available sources to improve the quality of communication of the group. In terms of dissemination of group or program communication through the media of brochures, posters, billboards, banners, while through IT Television, RRI, website, e-mail.